Enabling DSRC and c-V2X integrated hybrid vehicular networks: Architecture and protocol - Mir, Zeeshan Hameed; Toutouh, Jamal; Filali, Fethi; Ko, Young Bae (IEEE Access, 2020)
Emerging Vehicle-to-Everything (V2X) applications such as Advanced Driver Assistance Systems (ADAS) and Connected and Autonomous Driving (CAD) requires an excessive amount of data by vehicular sensors, collected, processed, and exchanged in real-time. A heterogeneous wireless network is envisioned where multiple Radio Access Technologies (RATs) can coexist to cater for these and other future applications. The primary challenge in such systems is the Radio Resource Management (RRM) strategy and the RAT selection algorithm. In this article, a Hybrid Vehicular Network (HVN) architecture and protocol stack is proposed, which combines Dedicated Short-Range Communication (DSRC) technology-enabled ad hoc network and infrastructure-based Cellular V2X (C-V2X) technologies. To this end, we address the design and performance evaluation of a distributed RRM entity that manages and coordinates Radio Resources (RR) in both RATs. Central to distributed RRM are adaptive RAT selection and Vertical Handover (VHO) algorithms supported by two procedures. (1) Measurement of Quality of Service (QoS) parameters and associated criteria to select the suitable RAT according to the network conditions. (2) Dynamic communication management (DCM) via implementing RR-QoS negotiation. The simulation results show the effectiveness of the proposed architecture and protocol suite under various parameter settings and performance metrics such as the number of VHOs, packet delivery ratio, and throughput, and latency.
Keywords: Dynamic communication; Heterogeneous wireless network; Multiple radio access technology (RATs); Packet delivery ratio; Proposed architectures; Quality of Service parameters; Radio resource management; RAT selection algorithms; C-V2X; DSRC; Hybrid vehicular networks; IEEE 802.11p; LTE; RAT selection; Vertical handover (VHO)